Minor actinides transmutation performance in a fast reactor. (September 2016) - Takeda, Toshikazu
Highlights: A method for calculating MA transmutation for individual nuclides has been proposed by introducing two formulas of the MA transmutation. One corresponds to the difference of MA amounts, and the other corresponds to the sum of the fission amounts and the plutonium production amounts. Using the method the MA transmutation was calculated for Np-237 and Am-241 in a fast reactor. The burnup period was changed from 1 year to 12 year. For the 1 year burnup a large amount of Am-242m, Cm-242 are produced from Am-241. The total MA transmutation amount increases with burnup time, but its gradient with respect to burnup time decreases after 9 years, and the transmutation amount by overall fission increases almost linearly with burnup time. However, after the 6 year burnup the fission contribution became large because of the large production of Pu isotopes from the original Am-241. In addition to the homogeneous loading of the MA nuclides into the cores, a heterogeneous loading of Am-241 to the blanket region was considered. Abstract: Results obtained in the project named "Study on Minor Actinides Transmutation using Monju Data", which has been sponsored by the Ministry of Education, Culture, Sports, Science and Technology in Japan (MEXT) are described. In order to physically understand transmutation of individual MA nuclides in fast reactors, a new method was developed in which the MAs transmutation is interpreted by two formulas. One corresponds to the difference of individual MA nuclides amounts before and after a burnup period, and the other is the sum of amount of fission of a relevant MA nuclide and the net plutonium production from the MA nuclide during a burnup period. The method has been applied to two fast reactors with MA fuels loaded in cores homogeneously and in a blanket region heterogeneously. Numerical results of MA transmutation for the two reactors are shown.